Family Development in Islam: The Foundation for Building a Sakinah, Mawaddah, and Rahmah Household - Bina Prima Panggayuh; Rezy Az Zahra; Dhia A’isy Putri; Kahleil Ryner Muharam; Muhammad Alhamrah Adam (Perkumpulan Dosen Fakultas Agama Islam Indramayu, 2026)
This study examines the role of Islamic-based family building in shaping households characterized by sakinah, mawaddah, wa rahmah in Indonesia. Through literature review of official national data and governmental policies principally from Statistics Indonesia (BPS) and the National Population and Family Planning Agency (BKKBN) the study evaluates family indicators (marriage, divorce, contraceptive participation) and the implementation of family building programs (family registration, premarital counseling, SIGA data system). The findings indicate that comprehensive family programs and data systems have the potential to support household resilience and quality. However, variation in access, socio-economic challenges, and suboptimal program reach suggest the need to strengthen faith-based and policy-based family building. Recommendations include reinforcing data–service integration, expanding the coverage of premarital counseling, and continuous evaluation to realize households of sakinah, mawaddah and rahmah.